Trading and Manipulation Around Seasoned Equity Offerings - Gerard, Bruno; Nanda, Vikram (Journal of Finance, 1993)
We investigate the potential for manipulation due to the interaction between secondary market trading prior to a seasoned equity offering (SO) and the pricing of the offering. Informed traders acting strategically may attempt to manipulate offering prices by selling shares prior to the SO, and profit subsequently from lower prices in the offering. The model predicts increased selling prior to a SO, leading to increases in the market maker's inventory and temporary price decreases. Further, since manipulation conceals information, the ratio of temporary to permanent components of the price movements is predicted to increase.